Pengaruh Proyek Literasi Media Sosial dalam Pembelajaran PPKn terhadap Peningkatan Kemampuan Berpikir Kritis - Edi Kusnadi; Deni Supriyadi; Natasya Rahmani Aimulloh; Zamzam Saepul Alam; Aldin Daemawan (Academy of Education Journal, 2026)
The rapid development of social media provides both opportunities and challenges for students in filtering information. In PPKn learning, innovative strategies are needed to help students understand civic issues critically. The social media literacy project serves as an approach that encourages students to analyze digital content reflectively and responsibly. Through project-based activities, students are trained to identify facts, opinions, hoaxes, and the social impacts of circulating information. This study aims to determine the influence of social media literacy projects in Pancasila and Citizenship Education (PPKn) learning on improving students’ critical thinking skills. This research employs a quasi-experimental method with a Nonequivalent Control Group Design. The research subjects consisted of two classes at SMA PGRI 2 Bandung, namely the experimental class (XI Social Science) and the control class (XI Science). The instruments used were tests administered before and after treatment (pretest and posttest). The results showed a significant difference between the pretest and posttest scores of both the experimental and control classes. The social media literacy project was also able to create active and engaging learning. The N-Gain score calculation for the experimental class using the social media literacy project showed an average value of 60.22%, categorized as fairly effective and approaching the upper limit toward the effective category. This indicates that the implementation of the social media literacy project in PPKn learning has a positive effect on improving students’ critical thinking skills. Thus, this approach can serve as an innovative alternative in developing 21st-century competencies, particularly in PPKn learning.